Becoming Rey Ileto: Language, History, and Autobiography - Rafael, Vicente L. (Archīum Ateneo, 2014)
Thisarticle inquires into the relationship between translation and autobiography in the work of Reynaldo Ileto. In Pasyon and Revolution, English and Tagalog are juxtaposed in a relationship of translation, indicating linguistic complexity and a politics of language that are deflected in Ileto’s later autobiographical writings. Yet, autobiography can also work like translation, but in the opposite direction of Pasyon and Revolution. Rather than loosen linguistic and social hierarchies, autobiography reinforces them. Ileto’s narrative tells of the splitting and substitution of selves, the excavation and overcoming of the father’s name, and the replacement of the “unfinished revolution” project with stories of gendered and generational succession.Keywords: translation • autobiography • Ileto • English • Tagalog